Pengaruh Promosi dan Pelayanan Terhadap Keputusan Masyarakat Menggunakan Jasa Pengiriman Pada PT. Pos Indonesia (Persero) Kota Medan - Safitri, Yani Devina; Sugianto, Sugianto (Universitas Labuhanbatu, 2022)
This study aims to examine and analyze the effect of promotion and service on people's decisions in using the delivery service of PT Pos Indonesia (Persero) Medan City. The research method used is a quantitative method. Data collection techniques were collected through a questionnaire with a sample of 80 people, then tested for validity and reliability. The data analysis technique used is the classical assumption test, multiple regression, t test, f test, and the Coefficient of Determination (R-Square).Based on the results of the analysis, it can be concluded, 1. Promotion affects people's decisions to use post office services, 2. Service affects people's decisions to use post office services, 3. Promotion and services simultaneously affect people's decisions to use post office services.